Asignación del carné de discapacidad y el delito de falsificación de documentos en el Ecuador - Alvarado-España, José Rodolfo; Paucar-Paucar, César Elías; Pupo-Kairuz, Alba Rosa (IUSTITIA SOCIALIS, 2021)
Asignación del carné de discapacidad y el delito de falsificación de documentos en el Ecuador